Voluntary standards as meso‐institutions: A Bayesian investigation of their relationships with transaction governance and risks. Issue 4 (15th March 2022) - Soregaroli, Claudio; Varacca, Alessandro; Ricci, Elena Claire; Platoni, Silvia; Tillie, Pascal; Stranieri, Stefanella
Abstract: Meso‐institutions offer a promising theoretical approach for assessing the way in which firms govern their activities and transactions while embedded in the macro‐institutional environment. The concept of meso‐institutions also offers theoretical support when evaluating a wide variety of voluntary standards that have been introduced within value chains in recent decades. Such tools can be considered meso‐institutions because of their features, and because of their role in translating general normative rules into specific mechanisms that delineate the domain of activities of supply chain agents. While various aspects of meso‐institutions have been investigated, little is known about their relationship with micro‐level structures and the determinants of firm's voluntary participation. The present paper investigates the association between a private standard, different forms of transaction governance in the supply chain, and the role that internal and external risks play in voluntary participation in the standard. The analysis draws upon secondary data taken from a representative sample of firms that form part of the European soybean supply chain. Our findings show that firms that participate in this standard have fewer hybrid forms and higher levels of spot markets. This suggests that some of the functions of hybrid forms are fulfilled by the meso‐institution. The results also show that risks associated with firm's behavioral uncertainty are more conducive to the participation in the standard than environmental‐related risks.